2008
DOI: 10.1063/1.2841327
|View full text |Cite
|
Sign up to set email alerts
|

“Massless” vector field in de Sitter universe

Abstract: In the present work the massless vector field in the de Sitter (dS) space has been quantized. "Massless" is used here by reference to conformal invariance and propagation on the dS light-cone whereas "massive" refers to those dS fields which contract at zero curvature unambiguously to massive fields in Minkowski space. Due to the gauge invariance of the massless vector field, its covariant quantization requires an indecomposable representation of the de Sitter group and an indefinite metric quantization. We wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
143
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(144 citation statements)
references
References 25 publications
1
143
0
Order By: Relevance
“…First, it is the only one among all non massless dS representations for which the Garidi mass vanishes, and it is part of an indecomposable structure issued from the existence of (constant) gauge solutions to (9.69). Secondly, it has been playing a crucial role in inflation theories, it is part of the Gupta-Bleuler structure for the massless spin 1 dS field (de Sitter QED) described by the UIR's Π + 1,1 [24], and it is the elementary brick for the construction of the massless spin 2 dS fields (de Sitter linear gravity) described by the UIR's Π + 2,2 [25]. Finally, the corresponding covariant quantum field theory requires a specific treatment due precisely to its indecomposable nature [26].…”
Section: Contraction Limits De Sitter → Minkowskimentioning
confidence: 99%
“…First, it is the only one among all non massless dS representations for which the Garidi mass vanishes, and it is part of an indecomposable structure issued from the existence of (constant) gauge solutions to (9.69). Secondly, it has been playing a crucial role in inflation theories, it is part of the Gupta-Bleuler structure for the massless spin 1 dS field (de Sitter QED) described by the UIR's Π + 1,1 [24], and it is the elementary brick for the construction of the massless spin 2 dS fields (de Sitter linear gravity) described by the UIR's Π + 2,2 [25]. Finally, the corresponding covariant quantum field theory requires a specific treatment due precisely to its indecomposable nature [26].…”
Section: Contraction Limits De Sitter → Minkowskimentioning
confidence: 99%
“…There exists another first-order field equation [8]: 24) which is invariant under the gauge transformation α →…”
Section: Massless Spinor Field Equations In De Sitter Spacementioning
confidence: 99%
“…There are two Casimir operators in the dS group and it has been shown that the massive scalar, vector, and spin-2 fields can be associated with the UIRs of the dS group [5,[20][21][22][23]. The massless fields can be associated with an indecomposable representation of the dS group [24]. The covariant quantum field theory for massive and massless conformally coupled scalar field in dS space have been studied in [5,25] and also for the massless minimally coupled scalar field in [26].…”
Section: Introductionmentioning
confidence: 99%
“…In this notation, the relationship with UIRs of the dS group becomes straightforward because the Casimir operators are easily identified with the field equation [11]. The transverse tensor field K αβ (x) is locally determined by the "intrinsic" field h µν (X) through…”
Section: Linear Field Equation In Ambient Space Notationmentioning
confidence: 99%